Two Cases of Cleft Lip and Other Congenital Anomalies in Wild Chimpanzees Living in Kibale National Park, Uganda. (November 2015) - Krief, Sabrina; Watts, David P.; Mitani, John C.; Krief, Jean-Michel; Cibot, Marie; Bortolamiol, Sarah; Seguya, Andrew G.; Couly, Gérard
Design: Observations of wild chimpanzees ( Pan troglodytes schweinfurthii ) were conducted in Kibale National Park, Uganda, at the sites of Sebitoli and Ngogo. Results: We report the first two cases of cleft lip in wild chimpanzees. Additionally, some other chimpanzees in the Sebitoli community show facial dysplasia and congenital anomalies, such as patches of depigmented hairs and limb defects. Conclusions: Cleft lip has been documented in several species of nonhuman primates, but much remains unknown about the occurrence of cleft lip and cleft palate in great apes, probably because such malformations are rare, wild apes are difficult to monitor and observe, and severe cases associated with cleft palates render suckling impossible and lead to early death of infants. The genetic basis of such defects in great apes warrants investigation, as does the possibility that environmental toxins contribute to their etiology in Kibale in ways that could affect humans as well.